Small cell carcinoma of the vulva: case report - Ana Correia; Elizabeth Castelo Branco; Paulo Correia; Marcos Guimarães; Luís Sá (Clinics and Practice, 2017)
Neuroendocrine tumours are rare in the gynaecologic tract, comprising approximately 2% of all gynaecological tumours. They have an aggressive behaviour and are a diagnostic and clinical challenge, due to their rarity and the lack of standardized therapeutic approaches. There are a few case reports. It is defined as a high-grade carcinoma exhibiting neuroendocrine differentiation. The authors describe the case of a 70-year-old woman, with vulvar neuroendocrine small cell carcinoma after superficial vulvectomy. The patient was submitted to a surgery with wide local excision and adjuvant radiation therapy. A review of the literature on this topic is also presented.